Notas sobre aves de la amazonia y orinoquia colombianas (1960)
In this paper a report is given concerning the distribution of some birds in the Colombian Amazonian and Orinoco drainages; also, some previous identifications are amended having at the present time more and better material recently collected and better facilities for studying. In addition, five new species. are recorded for the first time in the fauna of these regions and four new species and subespecies are added to the previous known list of Colombian birds.